2020
DOI: 10.1186/s12864-020-06868-5
|View full text |Cite
|
Sign up to set email alerts
|

Decoding the differentiation of mesenchymal stem cells into mesangial cells at the transcriptomic level

Abstract: Background: Mesangial cells play an important role in the glomerulus to provide mechanical support and maintaine efficient ultrafiltration of renal plasma. Loss of mesangial cells due to pathologic conditions may lead to impaired renal function. Mesenchymal stem cells (MSC) can differentiate into many cell types, including mesangial cells. However transcriptomic profiling during MSC differentiation into mesangial cells had not been studied yet. The aim of this study is to examine the pattern of transcriptomic … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…Compared with the P0 sample, many new functional subgroups appeared after the expansion of the cells [ 35 ]. This remarkable result indicates that, in the process of proliferation in vitro, the cells spontaneously differentiate and the identity characteristics of the cells change in many aspects.…”
Section: Resultsmentioning
confidence: 99%
“…Compared with the P0 sample, many new functional subgroups appeared after the expansion of the cells [ 35 ]. This remarkable result indicates that, in the process of proliferation in vitro, the cells spontaneously differentiate and the identity characteristics of the cells change in many aspects.…”
Section: Resultsmentioning
confidence: 99%
“…TO-GCN recommends to use normalized quantitative measures, e.g., TPM but also accepts normalized read counts. In this protocol, we use an RNA sequencing dataset from our previous study ( Wong et al., 2020 ) as an example. It is the dataset of mesenchymal stem cells differentiated into mesangial cells.…”
Section: Step-by-step Methods Detailsmentioning
confidence: 99%
“… Summary We describe steps to 1) identify ascending and descending monotonic key genes from time-ordered stem cell differentiation expression data, 2) construct time-ordered transcriptional regulatory networks, and 3) infer the involvement of transcription factors along the differentiation process. For complete details on the use and execution of this protocol, please refer to Wong et al. (2020) .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies have demonstrated that MSCs can either differentiate into renal cells in general[ 76 ] or specifically into kidney component cells such as renal epithelial cells[ 77 - 80 ], mesangial cells[ 81 , 82 ], and endothelial cells[ 83 , 84 ].…”
Section: Mscsmentioning
confidence: 99%